Results of surgical treatment of Hoffa fractures in pediatric population: 8-case series - Yuan Xiao; Clement Arthur; Xin Liu (Frontiers in Pediatrics)
ObjectivesHoffa's fractures are extremely rare in children. Very few cases have been published in connection with this condition. The present study highlights the healing outcomes of surgical treatment in pediatric Hoffa's fractures without direct comparison to conservative treatment.MethodsDuring this interval, on average, eight children with Hoffa fractures were treated in our department for 10.1 years. Seven had unicondylar fractures (4 lateral and 3 medial), and one had a bicondylar fracture. Unicondylar cases were operated upon with the lateral parapatellar approach, and a combination of direct lateral and medial access with PPA was applied for the bicondylar fracture. A Cannulated Compression Screw was used for fixation. The postoperative care included restricted weight-bearing for 10 weeks and removal of the fixation at 6 months. Follow-up was conducted on knee function and pain, and Letenneur scores were evaluated.ResultsThe bone union was obtained between 12 and 18 weeks. In the unicondylar cases, knee function was satisfactory, and most outcome measures showed supporting results. There was limited mobility in the bicondylar case and some mild varus; the Letenneur score was fair. Unicondylar fractures with bedding and early functional exercises did well in the long term, while the results of bicondylar fractures were poor.ConclusionThis study presents a surgical treatment approach for pediatric Hoffa fractures and monitors the results. However, it does not provide a comparison with conservative measures. The findings also offer insight into the surgical protocols needed for better long-term outcomes in children with Hoffa fractures.